2011
DOI: 10.2355/isijinternational.51.1057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Micro-particles in Iron Ore on the Granule Growth and Strength

Abstract: Pelletization tests were conducted using pulverized iron ore to record changes in pellet strength by changing the volume of micro-particles and ore types. The strength of pellets when completely dried can be explained by the volume of micro-particles in ore, and the greater the volume of micro-particles, the higher the strength of pellets. The rate of increase in pellet strength by micro-particles when completely dried varies depending on the ore type of micro-particles and the strength increases in the order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…For example, with the large amount of SiO 2 present in the iron ore, the pellet structure can be more rigid and stronger due to the stronger SiO 2 -bentonite interaction and the existence of hard SiO 2 in the structure. This point was reported previously by mechanical strength testing [8,9], and was complemented by the present work that studied the particle interaction aspect in detail by surface charge analysis. On the other hand, less amount of SiO 2 in the iron ore is requested for a blast furnace feed in terms of composition; but can lead loosely bound and weak pellets due to the weak interaction between Fe 2 O 3 and bentonite and fragile fine hematite presence with less structural support from SiO 2 .…”
Section: Zeta Potentialsupporting
confidence: 77%
See 1 more Smart Citation
“…For example, with the large amount of SiO 2 present in the iron ore, the pellet structure can be more rigid and stronger due to the stronger SiO 2 -bentonite interaction and the existence of hard SiO 2 in the structure. This point was reported previously by mechanical strength testing [8,9], and was complemented by the present work that studied the particle interaction aspect in detail by surface charge analysis. On the other hand, less amount of SiO 2 in the iron ore is requested for a blast furnace feed in terms of composition; but can lead loosely bound and weak pellets due to the weak interaction between Fe 2 O 3 and bentonite and fragile fine hematite presence with less structural support from SiO 2 .…”
Section: Zeta Potentialsupporting
confidence: 77%
“…Maeda et al [8] and Kawachi and Kasama [9] reported the importance of gangue minerals on the pellet compressive strength. For example, Maeda et al [8] observed noticeable difference in the dry compressive strength for the pellets produced with two different hematite ores hosting different gangue contents (SiO 2 wt.%, Al 2 O 3 wt.%).…”
Section: Introductionmentioning
confidence: 99%
“…It supports the selective granulation process 11) and standsupport sintering. 12) During the tests, binder 13) was used in the selective granulation line, and the stand-support function was reinforced by enhancing the effective height of the stand, to improve the permeability of the sintering bed. In addition, the blending ratio of brucite, the penetration length of ores, 14) and the bed height were increased to improve the melt properties during sintering.…”
Section: Manufacturing the Low-slag Sintered Oresmentioning
confidence: 99%
“…The direct reducibility and intensity of high-basicity sinter, which is the main raw material for blast furnace ironmaking, markedly influence the production efficiency of ironmaking [4,5]. The combustion characteristic of fuel in sintering mixture materials plays a decisive role in sinter quality [6,7]. Therefore, it is urgent to explore the combustion characteristics of solid fuel in the sintering process in order to provide a theoretical basis for improving the combustion efficiency, improving the quality of sinter and reducing the consumption of solid fuel [8].…”
Section: Introductionmentioning
confidence: 99%